2014
DOI: 10.7166/25-1-615
|View full text |Cite
|
Sign up to set email alerts
|

The Organisational Performance Impact Of ERP Systems On Selected Companies

Abstract: There is a need to determine the performance benefits that firms gain from enterprise resource planning (ERP) systems, and the factors that contribute to success. Consequently, the central research problem is:To determine the impact of ERP systems on organisational performance by analysing achieved ERP benefits within the framework of a suitable performance measurement system (PMS), and to investigate the association between critical success factors (CSFs) and ERP benefits.A list of expected ERP benefits and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…Similarly, a positive effect of the ERP implementation on the business performance has been seen by Hart and Snaddon (2014). They observed that some business benefits were achieved in the companies that implement the ERP system.…”
Section: Studies On the Support Of Business Processes Rolementioning
confidence: 86%
“…Similarly, a positive effect of the ERP implementation on the business performance has been seen by Hart and Snaddon (2014). They observed that some business benefits were achieved in the companies that implement the ERP system.…”
Section: Studies On the Support Of Business Processes Rolementioning
confidence: 86%
“…Teknoloji ve verilerden yararlanarak kuruluşlar pazarlama stratejilerini optimize edebilir, finansal kaynaklarını etkin bir şekilde yönetebilir ve insan kaynakları işlevlerinde en iyi yetenekleri çekip ellerinde tutabilirler. Bu entegrasyon, bir ku- ruluş içindeki farklı departmanlar arasında gelişmiş iletişim, işbirliği ve verimlilik sağlar (Hart & Snaddon, 2014). Ayrıca, iş bilgi sistemlerinin entegrasyonu, kuruluşların inovasyonu teşvik etmek ve pazarda rekabet avantajı elde etmek için otomasyonun, veri analitiğinin ve gelişmekte olan teknolojilerin gücünden yararlanmasını sağlar (Alotaibi, 2021).…”
Section: Sonuç Ve Tartışmaunclassified
“…Hal ini menunjukkan bahwa Implementasi enterprise resource planning meningkatkan kinerja organisasi. Hasil penelitian ini sejalan dengan penelitian yang dilakukan oleh (Hart & Snaddon, 2014;Eker, 2018;Zhang et al, 2012). Dalam menerapkan ERP terdapat lima manfaat yang akan diperoleh oleh perusahaan, yaitu manfaat operasional, manfaat manajerial, manfaat strategis, manfaat infrastruktur TI, dan manfaat organisasi, (Madapusi, 2012).…”
Section: Hasil Dan Pembahasan Karakteristik Respondenunclassified